Eligibility of Metastatic Pancreatic Cancer Patients for First-Line Palliative Intent nab-Paclitaxel Plus Gemcitabine Versus FOLFIRINOX. (October 2017) - Peixoto, Renata D.; Ho, Maria; Renouf, Daniel J.; Lim, Howard J.; Gill, Sharlene; Ruan, Jenny Y.; Cheung, Winson Y.
Abstract : Objectives: The PRODIGE and MPACT trials showed superiority of FOLFIRINOX and nab-paclitaxel plus gemcitabine (NG) over gemcitabine alone, respectively. However, both had strict inclusion criteria. We sought to determine the characteristics of patients with metastatic pancreatic cancer (MPC) which inform the appropriateness of first-line chemotherapy FOLFIRINOX and NG in routine practice. Materials and Methods: Patients with MPC who initiated palliative chemotherapy with gemcitabine from 2000 to 2011 at the British Columbia Cancer Agency were identified. Clinicopathologic variables and outcomes were retrospectively collected and compared among groups. Eligibility criteria for each regimen were in accordance with the respective pivotal phase III trials. Results: A total of 473 patients were included: 25% of the patients were eligible for FOLFIRINOX versus 45% for NG. Main reasons for FOLFIRINOX ineligibility were Eastern Cooperative Oncology Group (ECOG) performance status (PS)≥2 (56.5%), age older than 75 years (19.0%), and bilirubin>1.5× upper limit of normal (18.6%), whereas those for NG ineligibility were bilirubin > upper limit of normal (24.5%), ECOG PS≥3 (14.6%), and cardiac dysfunction (13.8%). Univariate analyses revealed that FOLFIRINOX and NG-eligible patients had longer median overall survival than their respective ineligible group (8.6 vs. 4.7 mo, P <0.001; 6.7 vs. 4.9 mo, P =0.008, respectively). After accounting for ECOG PS in the multivariate model, however, eligibility for either FOLFIRINOX or NG no longer predicted for better overall survival. Conclusions: The majority of patients with MPC are not candidates to either NG or FOLFIRINOX due to restrictive eligibility requirements. Specific trials addressing the unmet needs of protocol ineligible patients are warranted. Abstract : Supplemental Digital Content is available in the text.